Teleplay Criteria accordingto age Categories - Tazhibayev, Ғ.Қ.; Bildebekova, Ә.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
In this paper, the movie indexes used on television are provided in America and Kazakhstan. The legal norms introduced into the operation of movie indices are examined and the effectiveness of the age restriction system is examined. The efficiency of the domestic system is compared with the American system, which used the first movie indexes. The benefit and harm that the TV has provided to the person is discussed by experts and is still unable to come to a conclusion. After the Republic of Kazakhstan gained its independence, «freedom of expression» was broadcast in the media, as well as in the media, how many television channels that have left the society without filter